Baseline magnetic susceptibility measurements of rocks in the Precambrian basement terrain of southwestern Nigeria - C. Okpoli, Cyril; Michael A, Oladunjoye; Herrero-Bervera, Emilio (International Journal of Advanced Geosciences, 2024)
Petrological, mineralogical and magnetic susceptibility measurements have been studied within the southwestern Nigeria Precambrian basement rocks. Detail geological mapping and core sampling was done for mineralogical characterisation and magnetic susceptibility of the rock samples. Results of the petrographic analyses revealed: quartz, feldspars, hornblende, biotite and opaque (magnetite, ilmenite, maghemite, titanomaghemite) minerals; with minor component of ferromagnesian minerals like hornblende. Quartz, Microcline and Plagioclase alone constitute up to volume fractions 70 % of the rock in the thin section with plagioclase being the most dominant. The magnetic measurements have revealed that the volume susceptibilities K from the investigated samples range from 0.2 to 56,419 X10-6 [SI]. Charrnockites, Granite, biotite granite gneiss, banded gneiss, gneiss, aplite dike, granite, diorite granite gneiss ranges from: 10,059-56,419; 247-12856;0.2-129; 20.4-39.4; 14.1-22,366; 20-8250; 14-30233;4467-6641; and 632-26,921 X 10-6 [SI] respectively. Differential results in the frequency distribution is due varied composition of the paramagnetic (low magnetic susceptibility) and ferromagnetic (high magnetic susceptibility) grains in the rock specimen.